Toward process‐based conservation prioritizations for freshwater ecosystems. Issue 7 (8th July 2019) - Linke, Simon; Hermoso, Virgilio; Januchowski‐Hartley, Stephanie
Abstract: Over the last two decades, systematic conservation planning has been increasingly applied in terrestrial and marine systems. The approach has traditionally been lagging in freshwater environments, partly because considering unique ecological processes, such as connectivity and propagation of threats along river networks, is a key factor for conservation success in freshwater landscapes. This review highlights advances in freshwater planning in the last decade, but also discusses areas in need of increased efforts. Including riverine connectivity and disturbances are largely resolved topics. Both processes have been included in major conservation planning software packages and applied globally. Theoretical advances to connectivity in wetlands and groundwater systems have started to appear, but no encompassing framework has emerged. Spatial solutions to conservation planning in lakes do not yet exist. Some headway has been made when dealing with functional connectivity and genetic processes. For the latter, approaches have been developed to deal with cryptic biodiversity and to investigate the adequacy of conservation plans to include genetic diversity. Functional connectivity has been included in conservation plans in ephemeral waterscapes, and initial steps have been made to include migratory species in conservation prioritizations. Conservation planning in socio‐ecological landscapes is catching up with biophysical prioritizations. Multiple protection tiers have been realized in river conservation planning frameworks, and freshwater scientists are leading the charge in both multi‐objective planning and in including direct functional responses. We conclude that tight integration between ecological sciences and optimization approaches is needed to further process‐based conservation planning.